An unusual cause of upper gastrointestinal bleeding due to recurrent hepatocellular carcinoma: A case report. (2020) - Liu, Yuk Ho; Lo, Eugene Yee Juen; Lee, Kit Fai; Chong, Charing Ching Ning; Lai, Paul Bo San
Highlights: Hepatocellular carcinoma invading to gastrointestinal tract can present as bleeding. Invasion to gastrointestinal tract by hepatocellular carcinoma is relatively rare. Long term survival can be achieved by en bloc resection even if hepatocellular carcinoma invades into nearby organs. Abstract: Introduction: Upper gastrointestinal bleeding (UGIB) in patients suffering from hepatocellular carcinoma (HCC) is usually due to oesophageal or gastric varices secondary to portal hypertension. Very rarely, HCC can directly invade into the stomach or duodenum resulting in UGIB. Presentation of case: A 62-year-old man presented to the emergency department for haematemesis and tarry stool. He was a hepatitis B carrier and had received open radiofrequency ablation and wedge resection for HCC previously. Urgent endoscopy and contrast computed tomography confirmed recurrent HCC invading into the duodenum. The patient received radical resection and remained disease free for 7 years after the operation. Discussion: Direct invasion into gastrointestinal tract by HCC is rare. Different modalities of treatment have been reported in the literature with variable success. En-bloc resection should be considered if surgically feasible in order to achieve good haemostasis and possible long term survival. Conclusion: Upper gastrointestinal bleeding is a rare presentation of hepatocellular carcinoma and long term survival can be achieved by curative surgery.